2009
DOI: 10.1093/icesjms/fsp047
|View full text |Cite
|
Sign up to set email alerts
|

Global change and eutrophication of coastal waters

Abstract: Rabalais, N. N., Turner, R. E., Díaz, R. J., and Justić, D. 2009. Global change and eutrophication of coastal waters. – ICES Journal of Marine Science, 66: 1528–1537. The cumulative effects of global change, including climate change, increased population, and more intense industrialization and agribusiness, will likely continue and intensify the course of eutrophication in estuarine and coastal waters. As a result, the symptoms of eutrophication, such as noxious and harmful algal blooms, reduced water quality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
498
2
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 906 publications
(562 citation statements)
references
References 61 publications
6
498
2
15
Order By: Relevance
“…From a physical standpoint, warming of waters decreases dissolved oxygen and can cause changes in density, circulation patterns, and stratification (Scavia et al 2002;Harley et al 2006;Najjar et al 2010). From a biogeochemical standpoint, eutrophication-a world-wide problem of polluted estuaries (Bricker et al 2007)-is expected to worsen as WT rise (Scavia et al 2002;Rabalais et al 2009;Najjar et al 2010).…”
mentioning
confidence: 99%
“…From a physical standpoint, warming of waters decreases dissolved oxygen and can cause changes in density, circulation patterns, and stratification (Scavia et al 2002;Harley et al 2006;Najjar et al 2010). From a biogeochemical standpoint, eutrophication-a world-wide problem of polluted estuaries (Bricker et al 2007)-is expected to worsen as WT rise (Scavia et al 2002;Rabalais et al 2009;Najjar et al 2010).…”
mentioning
confidence: 99%
“…As eutrophic conditions in coastal waters are expected to become more prevalent in the future (Rabalais et al, 2009, Dalsgaard et al, 2013, the role of metal micronutrients, including those associated with groundwater, may become more important. Thus, more accurate groundwater discharge estimation to the Baltic Sea including the non-conservative transport of some trace elements into the sea are critical in order to establish the most reliable chemical budgets for the coastal zones and the entire Baltic Sea.…”
Section: Resultsmentioning
confidence: 99%
“…Other research has suggested that micronutrients, including B, Co, Cu, Fe, and Mo, can increase algal or cyanobacterial growth when concentrations of macronutrients (i.e., nitrogen and phosphorus) are already high and the system is already characterized as eutrophic (Zhang, 2000;Downs et al, 2008). As eutrophic conditions in coastal waters are expected to become more prevalent in the future (Rabalais et al, 2009), the role of metal micronutrients, including those associated with groundwater discharge, may become more important. In addition to supporting the growth of both desirable and undesirable primary producers, some metals can also be toxic to plants, animals, and humans.…”
Section: Discussion 41 Dissolved Metal Fluxes Via Groundwater To Thementioning
confidence: 99%
“…Examples of these include global, estuarine, and coastal marine nitrogen cycling Herbert, 1999;Pinckney et al, 2001;Rabalais, 2002;Ryther and Dunstan, 1971;Vitousek et al, 1997), fate modelling in soils, groundwater, and surface freshwater systems Seitzinger et al, 2010Seitzinger et al, , 2005Van Drecht et al, 2003;Wollheim et al, 2008), atmospheric emissions and deposition (Lee et al, 1997;Roy et al, 2012;van Vuuren et al, 2011), emissions from agriculture (Beusen et al, 2008;Bouwman et al, 2009Bouwman et al, , 2002Butterbach-Bahl and Dannenmann, 2011;Carpenter et al, 1998), emissions from wastewater (Van Drecht et al, 2009, loadings from rivers Kroeze et al, 2012;Seitzinger et al, 2010), or impacts from excess nitrogen inputs and eutrophication to marine ecosystems (Cloern, 2001;de Jonge et al, 2002;Kitsiou and Karydis, 2011;Rabalais et al, 2009;Smith et al, 2006.…”
Section: S12 Complementary Information On Modelling Anthropogenic Smentioning
confidence: 99%